Pricing and sustainability of urban real estate - Kauko, Tom (London : Routledge, 2018)
Urban sustainability has become a political and social agenda of global significance, of which real estate is an integral dimension. Sustainable urban development includes much more than green building' standards, yet in practice, other aspects such land use plans and locations are often overlooked. This book demonstrates that the issue of sustainable development stretches far beyond the hitherto dominating agenda based on green' (i.e. environmentally and ecologically sustainable) buildings. In doing so, it presents a novel framework based on the concept of economic sustainability of real estate locations, drawing connections with the global financial crisis and housing price bubble discourse. It argues for the need to better integrate social, cultural and economic dimensions into the real estate sustainability agenda. It also explores the role of location, and especially the image aspect therein. Trends in consumer choice are important to the way these dimensions are appreciated in decisions about investment, development, valuation and other activities of the production, consumption and governance of the built environment. This book will be of interest to private and public sector practitioners of real estate valuation as well as scholars of urban studies, geography, economics, urban planning and environmental studies.
Previously issued in print: 2016.
OCLC-licensed vendor bibliographic record.
Keywords: Real property -- Prices; Residential real estate; Sustainable development; SCIENCE / Earth Sciences / Geography